Prospects of anti-GD2 immunotherapy for retinoblastoma - Zhang, Xinlong; You, Wulin; Wang, Yuntao; Dejenie, Rebeka; Wang, Chenhao; Huang, Yan; Li, Jingjing (Frontiers in Immunology, 2024)
Retinoblastoma is the most common type of eye tumor in infants and children. Current treatments for retinoblastoma include intravenous chemotherapy, intra-arterial chemotherapy, intravitreal chemotherapy, cryotherapy, radiotherapy, and surgery. However, these treatments come accompanied by adverse effects such as the toxic side effects of chemotherapeutic drugs, post-operative complications including blindness after surgery, or other complications caused by radiotherapy. Immunotherapy is more promising for its low toxicity on normal cells and effectively improves the quality of life of patients. Disialoganglioside (GD2), a sphingolipid expressed on the surface of retinoblastoma, is a potential therapeutic target for retinoblastoma. We summarized immunotherapeutic approaches for both preclinical studies and clinical trials of GD2. An anti-GD2 monoclonal antibody (Dinutuximab), which has been approved for the treatment of high-risk neuroblastomas, has shown promising efficacy in improving patients’ prognosis. Additionally, chimeric antigen receptors (CAR)-T therapy, GD2 vaccines and nanoparticles are also potential therapeutics. Finally, we discuss the prospects and current limitations of these immunotherapeutic approaches for treating retinoblastoma, as well as how to address these problems.